Infectious dose‐dependent accumulation of live highly pathogenic avian influenza H5N1 virus in chicken skeletal muscle—implications for public health. (20th September 2017) - Vasudevan, G.; Vanamayya, P. R.; Nagarajan, S.; Rajukumar, K.; Suba, S.; Venketash, G.; Tosh, C.; Sood, R.; Nissly, R. H.; Kuchipudi, S. V.
Summary: Highly pathogenic avian influenza viruses (HPAIV) of H5N1 subtype are a major global threat to poultry and public health. Export of poultry products, such as chicken and duck meat, is a known source for the cross‐boundary spread of HPAI H5N1 viruses. Humans get infected with HPAI H5N1 viruses either by close contact with infected poultry or through consumption of fresh/undercooked poultry meat. Skeletal muscle is the largest soft tissue in chicken that has been shown to contain virus during systemic HPAIV infection and supports productive virus infection. However, the time between infection of a chicken with H5N1 virus and presence of virus in muscle tissue is not yet known. Further, it is also not clear whether chicken infected with low doses of H5N1 virus that cause non‐fatal subclinical infections continue to accumulate virus in skeletal muscle. We investigated the amount and duration of virus detection in skeletal muscle of chicken experimentally infected with different doses (10 2, 10 3 and 10 4 EID50 ) of a HPAI H5N1 virus. Influenza viral antigen could be detected as early as 6 hr after infection and live virus was recovered from 48 hr after infection. Notably, chicken infected with lower levels of HPAI H5N1 virus (i.e., 10 2 EID50 ) did not die acutely, but continued to accumulate high levels of H5N1 virus in skeletal muscle until 6 days post‐infection. Our data suggest that there is a potential risk of human exposure to H5N1 virus through meat from clinically healthy chicken infected with a low dose of virus. Our results highlight the need to implement rigorous monitoring systems to screen poultry meat from H5N1 endemic countries to limit the global spread of H5N1 viruses.